Command and control in the Afghan desert: a field study at a NATO headquarters. (10th April 2011) - Davids, Christiaan; Beeres, Robert; Grant, Tim
Managers gather information about the organisation and its environment to ensure that an organisation remains viable. The management of military units during deployment is known as command and control (C2). The C2 literature has focussed on applying technology to gain advantage over potential opponents. However, in today's military mission landscape other information is also needed. This article combines a technical and managerial perspective to analyse the operational management of a NATO headquarters in Afghanistan. Our research indicates that current C2 systems are not yet suited for delivering the required new intelligence because they emphasise the measurement of daily operations. C2 should bridge the gap between strategy and daily operations. Management tools drawn from the private sector, such as strategy maps and balanced scorecards, may be applied to enhance C2 systems to bridge operations and strategy. Furthermore, we argue that these management tools can adopt the operational measurement possibilities of C2 technologies to enhance their practical relevance.